2008
DOI: 10.1007/s12032-008-9095-6
|View full text |Cite
|
Sign up to set email alerts
|

Risk-adapted management for patients with clinical stage I non-seminomatous germ cell tumour of the testis

Abstract: Testis cancer is the most common cancer in young men and its incidence continues to rise. Even if prognosis is considered as good, a group with bad prognosis still remains. We aimed to evaluate whether two courses of chemotherapy after orchiectomy in patients with clinical stage I, non-seminomatous germ cell testicular tumour at high risk of relapse, will spare patients additional chemotherapy or surgery. High-risk patients had one or more of the following: preorchiectomy alpha-fetoprotein level of 80 ng/dl, 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 51 publications
2
4
0
Order By: Relevance
“…Other studies reported on a higher rate of metastatic disease in tumors containing less than 50% of teratoma elements (26). In our study collective higher pT-stage was associated with the presence of metastasis at diagnosis.…”
supporting
confidence: 68%
“…Other studies reported on a higher rate of metastatic disease in tumors containing less than 50% of teratoma elements (26). In our study collective higher pT-stage was associated with the presence of metastasis at diagnosis.…”
supporting
confidence: 68%
“…35 Several other studies using 2 cycles of BEP as primary treatment of stage I nonseminoma have similarly reported relapse-free survival rates .95%. 59,65,[69][70][71][72] However, late consequences of cisplatin-based chemotherapy, such as hearing damage and loss, cardiovascular conditions, hypertension, and neuropathy, have been reported during long-term follow-up. [73][74][75][76][77][78][79][80][81] Therefore, 1 cycle of BEP is recommended due to its lower toxicity.…”
Section: Primary Treatment Of Nonseminoma Stage I With Risk Factorsmentioning
confidence: 99%
“…Chemotherapy containing CDDP has been introduced as an adjuvant treatment option for micrometastatic disease, thereby reducing the risk of relapse to 2% (10). The percentage of EC component in the primary tumor is an important predictive factor for occult metastasis in stage I NSGCTs (7,(11)(12)(13), and adjuvant chemotherapy should be performed in such a way that resistance is minimized (14). Therefore, EC component control without induction of chemotherapeutic resistance is crucial for the appropriate clinical management of NSGCTs when considering the fact that ECs are a putative cancer stem component of NSGCT (15).…”
Section: Introductionmentioning
confidence: 99%